2015
DOI: 10.1007/s00701-015-2500-y
|View full text |Cite
|
Sign up to set email alerts
|

Safety and efficacy of microsurgical treatment of previously coiled aneurysms: a systematic review and meta-analysis

Abstract: Our meta-analysis suggests that surgical treatment is safe and effective. Our data indicate that aneurysms that are amenable to direct clipping have superior outcomes. Late surgery was also associated with better clinical outcomes. Surgery of recurrent posterior circulation aneurysms was associated with high rates of morbidity and mortality. Given the characteristics of the included studies, the quality of evidence of this meta-analysis is limited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(16 citation statements)
references
References 38 publications
1
15
0
Order By: Relevance
“…With the increasing advances in technology, a greater number of aneurysms can be managed via EVT today. However, aneurysms that are large (>10 mm), giant (>25 mm) or fusiform in morphology are associated with higher morbidity, mortality and recurrence rate when managed by EVT [14] , [15] , [16] . EVT also requires the administration of a dual anti-platelet regimen which may not be tolerated by all patients [15] .…”
Section: Discussionmentioning
confidence: 99%
“…With the increasing advances in technology, a greater number of aneurysms can be managed via EVT today. However, aneurysms that are large (>10 mm), giant (>25 mm) or fusiform in morphology are associated with higher morbidity, mortality and recurrence rate when managed by EVT [14] , [15] , [16] . EVT also requires the administration of a dual anti-platelet regimen which may not be tolerated by all patients [15] .…”
Section: Discussionmentioning
confidence: 99%
“…However, long term follow up of endovascularly treated aneurysms is known to reveal recurrence of aneurysms in up to 20%. 1 In the ISAT 2 trial 17.4% of patients who were treated with coiling required further procedures due to recurrence or incomplete occlusion of the aneurysms. The 10-year follow up of the ISAT cohort has revealed that the risk of aneurysmal re-bleeding, although low, is still higher than those treated with surgical clipping 3 .…”
Section: Introductionmentioning
confidence: 99%
“…In particular, clinicians seek strategies for identifying whether certain indications favor microsurgical clipping over repeat endovascular coiling. 19,22,23 However, with 100 only a limited amount of available data directly comparing the two treatments for recurrent 101 previously coiled aneurysms, neither have been shown to be superior to one another. 19,22,23 Re-embolization is often considered first when contemplating treatment for a recurrent or 104 residual previously coiled aneurysm because this procedure is thought to result in lower perioperative morbidity and mortality rates as well as lower peri-procedural 106 complications.…”
Section: Introduction 82mentioning
confidence: 99%
“…19,22,23 However, with 100 only a limited amount of available data directly comparing the two treatments for recurrent 101 previously coiled aneurysms, neither have been shown to be superior to one another. 19,22,23 Re-embolization is often considered first when contemplating treatment for a recurrent or 104 residual previously coiled aneurysm because this procedure is thought to result in lower perioperative morbidity and mortality rates as well as lower peri-procedural 106 complications. 4,10,22,[24][25][26][27][28][29][30] Nevertheless, aneurysm re-embolization comes with its own risks of coil compaction, shifting, malformation, extrusion and protrusion, as well as aneurysm residual, regrowth and rupture, peri-and post-operatively.…”
Section: Introduction 82mentioning
confidence: 99%